Measurement of lung volume and optimal oxygenation during high frequency oscillation. Issue 3 (May 1995) - Dimitriou, G.; Greenough, A.
Abstract : Twelve infants, median gestational age 27 weeks and postnatal age 1 day, were examined to determine whether oxygenation improves on transfer to high frequency oscillation (HFO). Lung volume was assessed before transfer to HFO by measuring functional residual capacity (FRC) using a helium gas dilution technique and specially designed infant circuit. On transfer to HFO, the inspired oxygen was initially kept constant, but the mean airway pressure (MAP) increased until maximum oxygenation was achieved (optimal MAP). The median FRC of the 12 infants before HFO was 8.1 ml/kg (range 4.7 to 28.7) and their median alveolar-arterial oxygen gradient (A-aDO2) 484 mm Hg. On transfer to HFO, oxygenation did not improve in two infants, but, overall, the A-aDO2 fell to a median of 289 mm Hg (p < 0.05). The median optimal MAP was 18.5 cm H2O (range 10.6 to 24.4) and this had an inverse correlation with the FRC before starting HFO (p < 0.01). The median change in MAP needed to maximise oxygenation on HFO also correlated negatively with FRC (p < 0.01).